INSTAGRAM FOR WRITING PRACTICE: STUDENTS’ PERCEIVED USEFULNESS AND EASE OF USE - Mardiyanah Nasta; Fatimah Hidayahni Amin; Hasriani G (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Social media has grown rapidly and affects our everyday life. It helps many aspects in our life, including students’ life. Instagram, one of the top platforms to use in the world recently, can be brought to the classroom for student’s learning purpose. Therefore, this research aims to specifically investigate students’ perception toward its usefulness and ease for writing practice. The sample was 31 out of 66 students in English Literature Study Program in the Faculty of Languages and Literature of one state university in Makassar. The data were collected by distributing questionnaire and by interviewing half of the participants. The items in the questionnaire were adapted from Davis (1989) theory about Technology Acceptance Model Articles. Supporting data were taken from the result of an interview. This research found that items in both perceived ease of use and perceived usefulness majority received a positive response. Students’ knowledge of Instagram is an advantage in using it as a writing practice medium. The distraction from the learning process is the downside that frequently happened while using it. This indicates that Instagram is a useful media for writing practice.